2018
DOI: 10.1159/000447222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Late Urinary Symptoms Following SBRT and SBRT with IMRT Supplementation for Prostate Cancer

Abstract: Background: Prostate cancer survivors commonly experience late-onset lower urinary tract symptoms following radiotherapy. We aimed to compare lower urinary tract symptoms in patients treated with stereotactic body radiotherapy (SBRT) to those treated with a combination of lower dose SBRT and supplemental intensity-modulated radiotherapy (SBRT + IMRT). Methods: Subjects with localized prostate carcinoma scheduled to receive SBRT or a combination of SBRT and IMRT were enrolled and followed for up to 2 years afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Efficient RT planning, use of dedicated rectal emptying and bladder filling protocols, omission of uninvolved portion of the seminal vesicles from the target volume, limiting of posterior PTV margins to limit the rectal volume being irradiated, delineation of urethra and limiting hot-spots inside it, daily image-guidance for VMAT, intrafraction motion tracking on CK by use of implanted fiducials, alternate-day treatment schedule for CK-SBRT, and delivering CK-SBRT before VMAT are some of the factors responsible for limiting late toxicity. A study by Feng et al [ 24 ] compared late GU toxicity between two schedules of SBRT alone versus a combination of IMRT and SBRT boost similar to our study and found lesser toxicity with the latter approach. Patients with prostate volume >50cc at baseline have been shown to experience greater GU toxicity [ 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Efficient RT planning, use of dedicated rectal emptying and bladder filling protocols, omission of uninvolved portion of the seminal vesicles from the target volume, limiting of posterior PTV margins to limit the rectal volume being irradiated, delineation of urethra and limiting hot-spots inside it, daily image-guidance for VMAT, intrafraction motion tracking on CK by use of implanted fiducials, alternate-day treatment schedule for CK-SBRT, and delivering CK-SBRT before VMAT are some of the factors responsible for limiting late toxicity. A study by Feng et al [ 24 ] compared late GU toxicity between two schedules of SBRT alone versus a combination of IMRT and SBRT boost similar to our study and found lesser toxicity with the latter approach. Patients with prostate volume >50cc at baseline have been shown to experience greater GU toxicity [ 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Urethra sparing with the same dose reductions was also used in both study arms. Nonetheless, there was a trend toward higher patient-reported mild GU discomfort with SDRT, and, consistently, the incidence of a transient late urinary flare syndrome was higher following SDRT. The cause of this self-limiting phenomenon probably resides in the dose to the bladder trigone, rather than in the urethra, and the implementation of stricter SDRT dose/volume constraints in this area is therefore warranted, as it may abrogate this late adverse effect .…”
Section: Discussionmentioning
confidence: 78%
“…Even though the cumulative incidence was high in this trial over time, most of the subacute toxicity resolved by the 2 year mark. Interestingly, this 12 month GU flare toxicity seemed to be lower in vHDRB compared to SBRT monotherapy (7.60 ± 0.42 and 9.53 ± 0.47, p = 0.003), as reported by Feng using the American Urological Association (AUA) symptom index [ 48 ]. Katz and Kang [ 31 ] may also support this, with lower late GU G3 toxicity seen in the vHDRB group compared to the SBRT monotherapy arm (2.3% versus 3.9%) and 2.3% versus 7.8% for late GU G2 toxicity.…”
Section: Emergence Of Sbrtmentioning
confidence: 72%